2001
DOI: 10.1088/0029-5515/41/10/310
|View full text |Cite
|
Sign up to set email alerts
|

First results from MAST

Abstract: MAST is one of the new generation of large, purpose-built spherical tokamaks (STs) now becoming operational, designed to investigate the properties of the ST in large, collisionless plasmas. The first six months of MAST operations have been remarkably successful. Operationally, both merging-compression and the more usual solenoid induction schemes have been demonstrated, the former providing over 400 kA of plasma current with no demand on solenoid flux. Good vacuum conditions and operational conditions, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
110
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 7 publications
3
110
0
Order By: Relevance
“…An apparent confirmation of these theoretical conclusions was found on early experiments at the Tokamak Fusion Test Reactor (TFTR) [7][8][9][10], where an upper limit for fast ion diffusivities was found at 0.1 m 2 · s −1 , an order of magnitude smaller than that of thermal ions. Recently, however, there has been renewed interest, triggered by experimental observations of anomalous redistribution of NBI ions at the Axial Symmetric Divertor EXperiment (ASDEX) Upgrade [11,12], at the Joint European Torus (JET) [13,14], at the Mega-Ampere Spherical Tokamak (MAST) [15,16], and at DIII-D [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…An apparent confirmation of these theoretical conclusions was found on early experiments at the Tokamak Fusion Test Reactor (TFTR) [7][8][9][10], where an upper limit for fast ion diffusivities was found at 0.1 m 2 · s −1 , an order of magnitude smaller than that of thermal ions. Recently, however, there has been renewed interest, triggered by experimental observations of anomalous redistribution of NBI ions at the Axial Symmetric Divertor EXperiment (ASDEX) Upgrade [11,12], at the Joint European Torus (JET) [13,14], at the Mega-Ampere Spherical Tokamak (MAST) [15,16], and at DIII-D [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The National Spherical Torus Experiment (NSTX) [2] and the Mega-Ampere Spherical Tokamak (MAST) [3] are presently the largest ST devices in the world fusion program. These devices have achieved both high confinement [4,5] and high β. NSTX has achieved both high toroidal-β, β T ≡ 2µ 0 p /B 2 T 0 up to 35%, and high normalized-β, β N ≡ β T aB T 0 /I P up to 6.5% mT/MA [6,7] using up to 7MW of deuterium Neutral Beam Injection (NBI) heating.…”
Section: Introductionmentioning
confidence: 99%
“…Wide angle images taken using fast cameras on NSTX [17] and MAST [21] have also shown that the edge light fluctuations in the plasma have a very long (many meter) correlation length along the magnetic field and a short (few-cm-scale) correlation length across the magnetic field B, similar to previous tokamak images on TFTR [22] and ASDEX [23]. Very long parallel correlation lengths have also been seen with probes in the scrape-off layer on JET [24].…”
Section: Introductionmentioning
confidence: 99%